Pengaruh Kualitas Sumber Daya Manusia dan Teknologi Informasi terhadap Kinerja Karyawan Melalui Komitmen Karyawan Sebagai Variabel Intervening (Studi Kasus di PT. Central Motor Wheel Indonesia – Pasuruan) - Nuril Hayati; Sumartik (Journal for Technology and Science, 2024)
Employee performance is influenced by several factors, one of which is employee commitment. When someone joins an organization, it is required to have a commitment in him. Commitment can support an employee to become a good team member who is willing to help the company to achieve its goals. High commitment can support an employee to become a good team member who is willing to help the company achieve its goals. The purpose of the following research is to determine the effect of the quality of human resources and information technology on employee performance through employee commitment at PT. Central Motor Wheel Indonesia. This study used a questionnaire, and used SPSS 25 software to analyze the data. Respondents in this study were 100 production/operational employees of PT. Central Motor Wheel Indonesia-Pasuruan. The results of this study prove that the quality of human resources affects employee performance, information technology affects employee performance, the quality of human resources affects employee commitment, information technology affects employee commitment, employee commitment affects employee performance, employee commitment mediates resource quality Humans on Employee Performance, and Information Technology has an effect on Employee Performance through Employee Commitment at PT. Central Motor Wheel Indonesia-Pasuruan